The Response of Ventral Tegmental Area Dopaminergic Neurons to Bupropion: Excitation or Inhibition? - Shirin Sadighparvar; Fereshteh Tale; Parviz Shahabi; Somayyeh Naderi; Firouz Ghaderi Pakdel (Basic and Clinical Neuroscience, 2019)
Introduction: Antidepressants can modulate brain monoamines by acting on pre-synaptic and postsynaptic receptors. Autoreceptors can reduce the monoamines effect on the somatodendritic or pre-synaptic regions despite its postsynaptic counter effects. The direct effect of some antidepressants is related to its temporal and spatial bioavailability in the vicinity of these receptors (still a matter of controversies). This research evaluated the direct effect of acute bupropion on the Ventral Tegmental Area (VTA) dopaminergic neuronal firing rate. Methods: Male Wistar rats were divided into intracerebroventricular and microiontophoretic groups with 14 subgroups (n=5 in each subgroup). Amounts of 1, 0.5, 0.1, 0.01, 0.001, and 0.0001 mol of bupropion (5 μL/3 min) were microinfused to the first group and then the ejected amounts of bupropion at -500, -300, -150, -50 nA of electrical currents (1 mol, pH=4.5, 5 min) were applied to the second group. The control and sham subgroups were studied in each group, too. The units with stable firing rates were extracted, and the effect of bupropion was evaluated statistically with a P value less than 0.05 as the level of significance. Results: The highest amount of bupropion in the intracerebroventricular application could excite 42% of the neurons and inhibit 56% of them, but the highest amount of microiontophoretic application of bupropion could inhibit 97.5% of the neurons. The neuronal response to bupropion was dose-dependent in all treated groups. Conclusion: The dual effects of intracerebroventricular bupropion on the VTA dopaminergic neurons but solo inhibitory effect of its microiontophoretic application reflect the intra-VTA and extra-VTA heterogenic cellular and molecular control over the dopaminergic outflow that can be mediated by different receptors. The dopamine autoreceptors on the VTA dopaminergic neurons have complex modulatory effects on the dopaminergic response.